2015
DOI: 10.1007/s12178-015-9306-7
|View full text |Cite
|
Sign up to set email alerts
|

Proximal humerus allograft prosthetic composites: technique, outcomes, and pearls and pitfalls

Abstract: The proximal humerus is the second most common location of primary bone sarcomas and a frequent location of benign locally aggressive primary osseous tumors. In contrast to other locations, tumors in this region impose significant challenges for local control and reconstruction. This is due to glenohumeral joint anatomic characteristics such as lack of intrinsic stability and dependence on dynamic and static stabilizers. In addition, the close proximity of the axillary nerve and axillary vascular bundle places… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Furthermore, several studies have shown allograft fracture, and not infection, to be the most common cause of failure and revision surgery in proximal humerus allograft reconstruction. 31 , 32 It is also important to note that fractures were the most common reason for revision surgery in our case series but were not found in the published literature. It is commonly thought that fractures are the number one reason for failure and subsequent revision surgery in allograft reconstructions, but this study shows that it is also important to assess nonunion and joint instability risk factors as well to prevent complications.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, several studies have shown allograft fracture, and not infection, to be the most common cause of failure and revision surgery in proximal humerus allograft reconstruction. 31 , 32 It is also important to note that fractures were the most common reason for revision surgery in our case series but were not found in the published literature. It is commonly thought that fractures are the number one reason for failure and subsequent revision surgery in allograft reconstructions, but this study shows that it is also important to assess nonunion and joint instability risk factors as well to prevent complications.…”
Section: Discussionmentioning
confidence: 77%
“…The second-most frequent complication is allograft fracture, which is a consistently prevalent event in allograft reconstruction of the proximal humerus in addition to subluxation. 32 Other complications from allograft reconstruction of the distal humerus include nerve injury and infections. Contrary to the common perception of the high risk of infection in this location because of soft-tissue coverage challenges, infection was not relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The association of allografts with prostheses theoretically allows matching the structural advantages from both reconstructions. Allograft's possibility to anchor surrounding soft tissues and therefore increase articular stability is combined with prostheses' durability; a more rigid construct is created and lower risk of fractures, subchondral collapses, and dislocations are achieved [ 128 ].…”
Section: Allograft-prosthesis Composite (Apc) Reconstructionsmentioning
confidence: 99%
“…After an intraarticular 1A resection of proximal humerus, an allograft-reverse prosthesis composite should be taken into consideration, remembering that this reconstruction requires good bone stock on the glenoid, integrity of the axillary nerve, and preserved deltoid function to guarantee satisfactory functional outcomes [ 128 ]. Surgical procedure assumes the use of an appositely prepared frozen allograft to replace proximal humerus and accommodate the prosthetic stem; the proximal part of the prosthesis is cemented to the graft and the distal stem is inserted in the native bone canal, either cemented or press-fitted.…”
Section: Allograft-prosthesis Composite (Apc) Reconstructionsmentioning
confidence: 99%
“…Technique: Prior to surgery, the planned resection of the humerus should be measured on the preoperative advanced imaging [23] . This is important to ensure that the appropriate length proximal humeral allograft is available during the surgery.…”
Section: Allograft Prosthetic Compositementioning
confidence: 99%